Propulsion systems for hybrid vehicles - Miller, John M. 1949- (IEE power and energy series, 2008)
Covers various aspects of the hybrid vehicle design, from its power plant and energy storage systems, to supporting chassis subsystems necessary for realising hybrid modes of operation. This book covers hybrid propulsion system architectures, propulsion system sizing, electric traction system sizing and design, and loss mechanisms.